2016
DOI: 10.1017/s1463423616000384
|View full text |Cite
|
Sign up to set email alerts
|

Providers’ perceptions of barriers and facilitators to disclosure of alcohol use by women veterans

Abstract: Providers (n=14) were recruited from primary care at two veterans Administration Women's Health Clinics in California, United States. An open-ended interview guide was developed from domains of the consolidated framework for implementation science. Interviews elicited primary care providers' perspectives on barriers and facilitators to women veterans' (who may or may not be using alcohol in harmful ways) disclosure of alcohol use during routine clinic visits. Interview data were analyzed deductively using a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Female veterans may find it difficult to disclose substance use to providers due to perceived stigma and shame associated with being a female substance user. 60 Additionally, female veterans with SUDs have higher rates of childhood sexual abuse, military sexual trauma, and domestic violence than female veterans without SUDs, and women with PTSD are particularly at risk of developing substance-related problems. 61 , 62 SUD treatments are often provided in groups made up primarily of male veterans.…”
Section: Introductionmentioning
confidence: 99%
“…Female veterans may find it difficult to disclose substance use to providers due to perceived stigma and shame associated with being a female substance user. 60 Additionally, female veterans with SUDs have higher rates of childhood sexual abuse, military sexual trauma, and domestic violence than female veterans without SUDs, and women with PTSD are particularly at risk of developing substance-related problems. 61 , 62 SUD treatments are often provided in groups made up primarily of male veterans.…”
Section: Introductionmentioning
confidence: 99%
“…A study involving provider's perceptions of barriers to disclosure of alcohol use by women veterans found that practitioners who had developed a good rapport with their patients felt more confident with SBI. The established therapeutic relationship allowed providers to be more forthcoming with questions and probe deeper when they sensed a patient's reluctance to disclose HAU (Abraham et al, 2017). The findings from this study call into question whether SBI can be effective when applied in acute care settings like same-day clinics/EDs.…”
Section: Avoidance Biasmentioning
confidence: 87%
“…In the presence of chronic medical/mental health conditions, SBI for HAU is viewed as less relevant to other patient care issues (Abraham et al, 2017;Goldstein et al, 2015;McNeely et al, 2018). A qualitative study involving 67 primary care providers (PCPs) conducted in two U.S. urban hospital settings found that PCPs demonstrated inconsistent screening practices.…”
Section: Avoidance Biasmentioning
confidence: 99%
“…34 Although women consume less alcohol than men, the sex/gender difference has been decreasing in recent years. 35 In studies of unhealthy alcohol use, women experience greater alcohol use related stigma than men, 36,37 which could impact how providers respond to 38,39 and document 40 use among women. More research is needed to understand sex/gender differences in substance use reporting and its documentation in the EHR.…”
Section: Discussionmentioning
confidence: 99%